Ancient Egyptian phonology - Allen, James P., 1945- (Cambridge University Press, 2020)
"In Ancient Egyptian Phonology, James Allen studies the sounds of the language spoken by the ancient Egyptians through application of the most recent methodological advances for phonological reconstruction. Using the internal evidence of the language, he proceeds from individual vowels and consonants to the sound of actual ancient Egyptian texts. Allen also explores variants, alternants, and the development of sound in texts, and touches on external evidence from Afroasiatic cognate languages. The most up to date work on this topic, Ancient Egyptian Phonology is an essential resource for Egyptologists and will also be of interest to scholars and linguists of African and Semitic languages"--